The impact of liquidity risk, credit risk and operational risk on the performance of Iraqi private banks - Al Yousuf, Noor Hashim Mohammed (2016)
The main objectives of this research is to study the effect of liquidity risk, credit risk and operational risk on the performance of private banks in Iraq for the period 2009 to 2014. This study especially focus on Iraqi commercial private Banks. The dependent variables for bank performances are measured by return on asset (ROA) and return on equity (ROE), and independent variables which are, liquidity risks are measured by liquidity ratio and calculate as liquid asset to total asset, credit risks are measured by non-performing loan ratio and operational risks are measured by earnings before interest and tax divide on total asset. This study employs panel data regression analysis of fixed effects and random effects models. Furthermore, the results show that liquidity risk was found having positive significant relationship with ROA and ROE. While credit risk has negative significant relationship with ROA, and negative insignificant relationship with ROE. However, operational risk was found to have significant and negative effect on ROA. While operational risk was significant and positively related to ROE.